IDENTIFICATION OF HELMINTH AND ZOONOSIS POTENTIAL IN EEL (Anguilla spp.) FROM LINDU LAKE, SIGI DISTRICT - ARIF RAHMAN JABAL; UMI CAHYANINGSIH; RISA TIURIA; ARINI RATNASARI (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2020)
Parasitic helminth infection in eel (Anguilla spp.) From the Lindu Lake affects fish health and fish weight. The purpose of this study identified parasitic helminth and zoonosis potential in eels From Lake Lindu. The helminth parasitic examinations were collection of eels, observation, measurement, identification of helminth, and staining nematode and trematode used clove oil and Semichon Acetocarmine. The species of helminth found were Anisakis sp. 44%, Anguillicola sp. 2%, and digenean 23%. The potential zoonotic is Anisakis sp., among other Helminth on eels. Eel consumption must cook because there are Anisakis sp. that have the potential for zoonosis.Keywords: Identification, Helminth Parasitic, Eel